2009
DOI: 10.1111/j.1547-5069.2009.01281.x
|View full text |Cite
|
Sign up to set email alerts
|

Human Rights Barriers for Displaced Persons in Southern Sudan

Abstract: Results help nurses understand the intersection between health and human rights as well as approaches to advancing rights in a culturally attuned manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…They are not allowed to make any important decisions in the family as all authority resides with the males—husbands, brothers, fathers, and uncles. Pavlish and Ho (2009) recently found that the customary law is still commonly applied in South Sudan. The authors assert that customary law most often violates women's human rights.…”
Section: Discussionmentioning
confidence: 99%
“…They are not allowed to make any important decisions in the family as all authority resides with the males—husbands, brothers, fathers, and uncles. Pavlish and Ho (2009) recently found that the customary law is still commonly applied in South Sudan. The authors assert that customary law most often violates women's human rights.…”
Section: Discussionmentioning
confidence: 99%
“…Many published reports describe the translation process but do not report the qualifications or background of the translators themselves, how they were trained, the nature of their role and relationship with the researcher, or what compromises were made in the translation process to accommodate the specific cultural context of the targeted group. For example, Pavlish and Ho (2009) described the translation process as they interviewed key informants about human rights barriers in Southern Sudan: "after each question, the language interpreter translated participants' responses from Arabic into English while both researchers took extensive notes" (p. 285). As in many other published reports, the language interpreter is not mentioned again.…”
Section: Functional Equivalencementioning
confidence: 99%